Finite Element Analysis and Experimental Study on the Vibration Characteristic of the Vertical Column of Cycloid Gear Grinding Machine - Wang Huiliang; Fang Yi; Ren Xiaozhong (Jixie chuandong)
In order to study the vibration characteristic of vertical column of cycloid gear grinder,the three-dimensional solid model is established based on the vertical column component of cycloid gear grinder,and the pre-stress modal analysis is carried out based on the finite elements software ANSYS simulation. The natural frequency and corresponding vibration mode of the component are obtained. To study the real vibration characteristic of the vertical column,the vibration test platform is set up. Then the time-frequency characteristic of the collected data are analyzed,and the vibration mechanism of the vertical column is explored. The experimental results show that the vertical column is better in the low order frequency characteristic,and compared with the free working conditions under the same direction,the maximum vibration amplitude of the corresponding peak at the same frequency is not more than 4. 7%. Finally,the rationalization proposal for design and optimization of the vertical column are put forward from the vibration.